Validity and Reliability of the Nurse Preparedness Questionnaire in Facing Emerging Infectious Diseases - Ida Ayu Agung Laksmi; I Made Dwie Pradnya Susila (KHD-Production, 2022)
Nurse preparedness is a factor that needs to be considered in order to suppress work safety in the face of the COVID-19 pandemic. Early nursing intervention plays an important role in the prevention, preparedness, and response to the impact of the COVID-19 pandemic and other emerging infectious diseases. A nurse preparedness questionnaire about emerging infectious diseases needs to be compiled as an instrument that can measure preparedness related to unpredictable emerging infectious diseases. The aim of this study was to analyze the validity and reliability of the nurse preparedness questionnaire in dealing with emerging infectious diseases in Bali. This research method is a cross-sectional study involving all nurses in the emergency department at Klungkung Hospital as many as 30 people. Conducting a literature review and adopting the WHO COVID-19 preparedness questionnaire developed the instrument. The questionnaire consists of 4 dimensions with a total of 28 statement items covering the dimensions of knowledge on preparedness for emerging infectious diseases, dimensions of facility preparedness and response readiness in triage, dimensions of the effective response of nurses, and dimensions of preparedness and readiness of nurses for personal protective equipment. The stratified scale in this questionnaire uses a modified Likert scale with 4 answer choices of answers choices (4) strongly agree (3) agree (2) disagree and (1) strongly disagree. In instrumental testing, all 28 items of the instrument were confirmed through content validity (Pearson Product Moment). Using internal consistency reliability, the study found reasonable inter-item reliability for all items (Cronbach’s α: > 0.90)